Comparison Between The Efficacy of Different Medical Herbs on Cryptosporidium spp. - Kadir, Mohammed Abdul-Aziz; Al-Alousi, Tawfiq Ibrahim; AI-Sawah, Diab A. (Journal of the Faculty of Medicine Baghdad, 2008)
Objectives:The study was planned to show the effect of different medicinal plants extracts on Cryptosporidium spp.Materials and Methods:The experimental study was performed in laboratory mice to show the efficacy of different medical plants extracts (Achillea fragrantissima, Artemisea herba-alba,Cardaria draba, Mentha longifolia , Olea europea, Prosopis farcta, Punica granatum, Teucrium polium and Ziziphus spina-charisti on shedding of Cryptosporidium spp. oocysts.Results:In a study on the effect of medical plant extracts on the shedding of oocysts in mice, it was found that different medical plants extracts decrease the shedding ofCryptosporidium oocysts in mice. Using 250 mg / kg B.W., route it was shown that the efficacy of Prosopis farcta (67.6 %) followed by Artemesia herba alba (57.7 %), Cardaria draba (35.9 %) and the lowest was Teucrium polium (12.7 "/o) but Mentha longifolia had no effect. It was also shown that the efficacy of medical plants extracts (500 mg / kg B.W.) was higher than (250 mg / kg B.W.) in shedding of the parasite oocysts. In a study of the effect of plant extracts on the development of oocysts of Cryptosporidium in the macrophage in Rpm medium, it was found that the efficacy of Punica granatum (75.9%) was highest, followed by Prosopis farcta (67.1%) and Artimesia herba- alba (55%).Conclusions:The medical plant extracts have an effect on Cryptosporidium spp. Infection in albino mice. The possibility of studying the therapeutic research onCryptospridium spp. in RPM medium.